Efficacy and safety of prophylactic levetiracetam in supratentorial brain tumour surgery: a systematic review and meta‐analysis. (24th April 2016) - Pourzitaki, Chryssa; Tsaousi, Georgia; Apostolidou, Eirini; Karakoulas, Konstantinos; Kouvelas, Dimitrios; Amaniti, Ekaterini
Abstract : Aims: The aim of this study was to perform an up‐to‐date systematic review and meta‐analysis on the efficacy and safety of prophylactic administration of levetiracetam in brain tumour patients. Method: A systematic review of studies published until April 2015 was conducted using Scopus/Elsevier, EMBASE and MEDLINE. The search was limited to articles reporting results from adult patients, suffering from brain tumour, undergoing supratentorial craniotomy for tumour resection or biopsy and administered levetiracetam in the perioperative period for seizure prophylaxis. Outcomes included the efficacy and safety of levetiracetam, as well as the tolerability of the specific regimen, defined by the discontinuation of the treatment due to side effects. Results: The systematic review included 1148 patients from 12 studies comparing levetiracetam with no treatment, phenytoin and valproate, while only 243 patients from three studies, comparing levetiracetam vs phenytoin efficacy and safety, were included in the meta‐analysis. The combined results from the meta‐analysis showed that levetiracetam administration was followed by significantly fewer seizures than treatment with phenytoin (OR = 0.12 [0.03–0.42]: χ 2 = 1.76: I 2 = 0%). Analysis also showed significantly fewer side effects in patients receiving levetiracetam, compared to other groups ( P < 0.05). The combined results showed fewer side effects in the levetiracetam group compared to the phenytoin group (OR = 0.65 [0.14–2.99]: χ 2 = 8.79: I 2 = 77%). Conclusions: The efficacy of prophylaxis with levetiracetam seems to be superior to that with phenytoin and valproate administration. Moreover, levetiracetam use demonstrates fewer side effects in brain tumour patients. Nevertheless, high risk of bias and moderate methodological quality must be taken into account when considering these results.